Effect of heat treatment on the physical properties of Ni-Mn-Ga alloy - Kok, Mediha; Aydogdu, Ylidirim (Elsevier Science Bv, 2012)
In this study, the effect of heat treatment on physical properties such as crystal structure, transformation temperatures, thermodynamic behavior and activation energy of Ni50.5Mn29.5Gd20 (at.%) off-stoichiometric Heusler alloys was investigated. The heat treatments were conducted at 800 degrees C, 900 degrees C and 1000 degrees C for 2 h in argon atmosphere and then samples were quenched in ice brine. It has been found that the heat treated alloys possess a coexistence phase of martensite and gamma (gamma) phases while the untreated alloy is gamma phase free. Moreover, elevating the annealing temperature resulted in increased martensitic transformation temperatures. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ferromagnetic; Ni-Mn-Ca; Alloy; Heat; Phases; Martensite